2013
DOI: 10.1002/dta.1590
|View full text |Cite
|
Sign up to set email alerts
|

The poppy seed defense: a novel solution

Abstract: A major toxicological challenge is distinguishing whether morphine in urine, in the absence of 6-monoacetylmorphine (6-MAM), originates from 'street' heroin use or poppy seed ingestion. Manufacturing byproducts from the synthesis of illicit heroin include those that originate from the reaction of acetic anhydride with the alkaloid impurity, thebaine, which undergoes skeletal rearrangement, resulting in compounds with a 2-(N-methylacetamido)ethyl side-chain. The hypothesis that the tertiary amide in this side-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Others reported markers in heroin, such as acetylcodeine, with a similar outcome [3,14]. A recent report by Chen et al appears more promising [15]. These investigators employed a sensitive liquid chromatography tandem mass spectrometric method to identify an acetylated thebaine glucuronide (3,6-dimethoxy-4-acetoxy-8-[2-(N-methylacetamido)ethyl]phenanthrene; abbreviated ATM4G) in 16 of 22 urine specimens produced by 22 heroin addicts who had 6-AM <10μg/L in each specimen and total morphine (morphine-3-glucuronide and morphine) concentrations >300μg/L in 17 of the specimens.…”
Section: Resultsmentioning
confidence: 91%
“…Others reported markers in heroin, such as acetylcodeine, with a similar outcome [3,14]. A recent report by Chen et al appears more promising [15]. These investigators employed a sensitive liquid chromatography tandem mass spectrometric method to identify an acetylated thebaine glucuronide (3,6-dimethoxy-4-acetoxy-8-[2-(N-methylacetamido)ethyl]phenanthrene; abbreviated ATM4G) in 16 of 22 urine specimens produced by 22 heroin addicts who had 6-AM <10μg/L in each specimen and total morphine (morphine-3-glucuronide and morphine) concentrations >300μg/L in 17 of the specimens.…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, poppy seed ingestion study performed by Chen et al [8] revealed similar results even following consumption of poppy seeds containing up to 60 μg thebaine. Consequently, the prerequisites for the formation of ATM4G following consumption of poppy seed products were met.…”
Section: Discussionmentioning
confidence: 64%
“…[8] Poppy seed products and alkaloid extraction Unground blue poppy seeds were obtained from Rapunzel Naturkost GmbH (Legau, Germany), Edeka (Hamburg, Germany) and Seeberger (Ulm, Germany). The reference materials 6-AC, papaverine, noscapine, 6-MAM, morphine, and codeine as well as the internal standards 6-MAMd 3 , morphine-d 3 , and codeine-d 3 were obtained from Cerilliant (Round Rock, TX, USA).…”
Section: Methods and Materials Chemicals And Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite multiple efforts, no unambiguous markers were identified, nor has a poppy seed consumption limit or analytical cutoff been developed to differentiate poppy seed ingestion from heroin or morphine use. A recent study suggested that urinary ATM4G, a glucuronide metabolite of a byproduct from the synthesis of illicit heroin (thebaine with a 2(N-methylacetamido)ethyl side-chain), can differentiate the source of opiate intake [5]. …”
Section: Introductionmentioning
confidence: 99%